2010
DOI: 10.3109/08941930903469375
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Nigella Sativa on Intestinal Ischemia-Reperfusion Injury in Rats

Abstract: Our results suggest that NS treatment protected the rat's intestinal tissue against intestinal ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Its scavenging actions have been demonstrated in a number of tissues [40,41,42,58], although the protection for ovaries has not been evaluated in detail. In the present study, a reduction in SOD and GSH levels and an increase in MDA levels occurred after a period of ischemia followed by reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its scavenging actions have been demonstrated in a number of tissues [40,41,42,58], although the protection for ovaries has not been evaluated in detail. In the present study, a reduction in SOD and GSH levels and an increase in MDA levels occurred after a period of ischemia followed by reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical and animal studies have shown that an extract of NS has many therapeutic effects, including antiproliferative, anti-inflammatory, antitumor, anticancer, multiple myeloma, antibacterial, estrogenic, and antioxidant activity [32,33,34,35,36,37,38,39]. Experimental studies have also revealed that thymoquinone has protective effects against I/R injury in the intestine [40], liver [41], kidney [42], and testicular torsion [43]. It has also been reported that the crude NS seeds did not produce any adverse side effects at the doses tested [44].…”
Section: Introductionmentioning
confidence: 99%
“…Black cumin oil (BCO) contains more than 30% fixed oil and 0.4-0.45% volatile oil. In volatile oil analysis, many components have been characterized, but the major ones are thymoquinone (27.8-57.0%), q-cymene (7.1-15.5%), carvacrol (5.8-11.6%), t-anethole (0.25-2.3%), 4-terpineol (2.0-6.6%), and longifoline (1.0-8.0%) [18,19]. Nigella sativa oil is so beneficial due to its content of over 100 components such as aromatic oils, trace elements, vitamins, and enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…There is no correlation between any of the biochemical parameters and histopathological damage score. In an experimental ischemia reperfusion study involving rats, Terzi A et al observed that OSI and TOS increased in ileum tissue in rats exposed to ischemia reperfusion, while TAS decreased (22 …”
Section: Resultsmentioning
confidence: 99%